Life Cycle Greenhouse Gas Emission Assessment of Photovoltaic System in Indonesia - Oktoviano Gandhi; Carlos D Rodríguez-Gallegos; Wenjie Zhang (Research Synergy Press, 2022)
Climate crisis is arguably the biggest challenge that the world is currently facing. Extreme weather events are becoming more frequent while the continuous rise in sea level is putting billions of lives will be at risk. Solving the climate crisis requires global carbon emission to peak by 2025, which means that carbon-intensive fossil fuels must be replaced by low-carbon renewable sources in fulfilling our energy needs. Solar energy, due to its abundance, rapidly decreasing cost, and low carbon emission, is one of the most promising energy sources. Many studies have calculated and compared the life cycle greenhouse gas (GHG) emissions of solar photovoltaic (PV) systems with conventional fuel generation. Nevertheless, the life cycle GHG emission values are affected by many location- and technology-dependent factors. This work provides an up-to-date and realistic assessment of the life cycle GHG emission for PV systems in Indonesia through thorough literature review and harmonization according to Indonesian parameters. The study shows that PV GHG emission of 37.3-64.3 gCO2eq/kWh are much lower than the current emission intensity of the Indonesian power sector. By fulfilling rising electricity demand using PV, up to 654 MtCO2eq can be avoided annually by 2050.